Preventive measures to combat administrative and financial corruption in UAE - Al-Hayas, Khawla Musa Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to shed light on preventive measures to combat administrative and financial corruption, We highlighted the nature of administrative and financial corruption، its types and its impact on public funds in the first demand، and then outlined the controls and dimensions of the protection of public funds and the preventive measures of administrative and financial corruption in the second demand، and shed light on the definitions of both administrative corruption and financial corruption. Is to bribe، gain from the public office، and then identified the types of financial corruption، which is the misappropriation of public funds، and then directed to the impact of administrative corruption on public funds and the mingled with the names. We discussed the differences between corruption and corruption، corruption and government. We discussed the difference between corruption، embezzlement of public funds، aggression and treachery. We also discussed the controls and dimensions of the protection of public funds which must be achieved by States in order to save public money. If it contains the public function and we have addressed the controls on the protection of public funds in the United Arab Emirates. We also discussed the measures and preventive measures to combat administrative and financial corruption، the most important of which is the rise in the level of job performance or productive efficiency of the job، the care of the public employee، the provision of the necessary rights and guarantees، and the care and respect of the job. Finally، we made some recommendations to reduce the phenomenon of administrative and financial corruption.
Keywords: preventive measures; combating; administrative corruption; financial corruption